Implementasi Aplikasi Citrix System Studi Kasus PT De-Well Logistic Indonesia - Sansprayada, Arfan (LPPM STMIK ANTAR BANGSA, 2018)
Abstract — This app describes the details of the information flow about how the order starts order begins until the process is complete. Logistic services or delivery of goods is an increasingly advanced business and growing. Although it looks simple and common in the logistics business but who would have thought if the potential market is extraordinary. Along with the increasing demand or the need for consumers to deliver goods through logistics services, it is necessary a system to provide convenience to consumers to know delivery service (via air / landline), heavy charge (Actual / volmetric), details of the cost for goods with special treatment ( insurance / wood packing), before they decide to ship the goods to a logistic service. The advantages and benefits of the application to be built is later this application can be used to facilitate the calculation of cost, so there is no cheating in the weight calculation. In addition, applications can be used as a means of price comparison and expedition services with other services. PT De-Well Logistik Indonesia is one of the companies engaged in forwarding where the service company that serves the needs of export and import. The company providing freight forwarder is a subsidiary of Dewell Shangai located in china. With the application of citrix system application is expected to provide convenience and facilitate employees in doing all the activities in achieving goals for the company.Intisari — Penulisan ini mengimplementasikan tentang aplikasi citrix dengan studi kasus pada PT De-Well Logistic Indonesia. Sebuah perusahaan yang bergerak dibidang eksport dan import yaitu perusahaan yang mengurusi pengiriman barang berupa container atau petikemas baik dalam partai besar ataupun partai kecil. Aplikasi ini menggambarkan detail tentang alur informasi tentang tata cara dimulainya order tersebut dimulai sampai proses selesai. Jasa logistic atau pengiriman barang merupakan bisnis yang semakin maju dan berkembang. Walau terlihat sederhana dan biasa dalam bisnis logistic tapi siapa sangka jika potensi pasarnya luar biasa. Seiring dengan meningkatnya permintaan atau kebutuhan konsumen untuk mengirimkan barang melalui jasa logistic, maka diperlukan suatu system untuk memberikan kemudahan kepada konsumen untuk mengetahui layanan pengiriman (via udara/darat), charge berat (Aktual/volmetrik), rincian biaya untuk barang dengan perlakuan khusus (asuransi/packing kayu), sebelum mereka memutuskan untuk mengirimkan barang kepada suatu jasa logistic. Keunggulan dan manfaat aplikasi yang akan dibangun adalah nantinya aplikasi ini dapat digunakan untuk mempermudah penghitungan cost, sehingga tidak ada kecurangan dalam penghitungan berat.Kata Kunci : Logistik, Sistem, Eksport, Import.